Intercultural Acculturation of Islam, West, and Nusantara Cultures at Cipaganti Mosque Bandung - Husna Izzati; Andiyan Andiyan; Irfan Aldyanto (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2021)
Islam has a powerful influence on people’s lives, especially in Indonesia, including in a mosque architecture, where influenced by several cultures. The mosque, a place for worship for Muslims, is a building that often experiences acculturation in its building design. Cipaganti Mosque, one of the oldest mosque in Bandung, might be identified by its Java style, Sunda style, and also Europe style. However, this mosque also reflects Islamic culture which include all architectural aspects of the building. This research aims to examine the extent to which Islamic culture exists in this mosque, and how the acculturation of the three cultures with Islamic culture becomes an inseparable part of the building architecture. Using a qualitative method with a descriptive approach divided into several stages, namely observation, documentation, and data analysis, the research was able to obtain a comprehensive and objective of a variety of cultural acculturation in Cipaganti Mosque building. Finally, found that the acculturation of Islamic culture in mosques was explicit and was found to be comprehensive from all aspects of the building. This acculturation, consisting of Islamic culture, Western European culture, Javanese culture, and Sundanese culture, makes Cipaganti Mosque has a unique architectural concept and makes this building one of the cultural heritage buildings in the city of Bandung.